Pengaruh pemberian hesperidin dalam pakan broiler terhadap kolesterol, LDL, HDL pada darah dan daging serta analisis usaha dalam penerapannya pada industri peternakan - Nanda Oktabitha; Wiwik Misaco Yuniarti; Mohammad Anam Al Arif; Bambang Sektiari L; Sri Hidanah; Eduardus Bimo Aksono (Fakultas Pertanian Universitas Majalengka, 2026)
This study aimed to evaluate the effect of dietary hesperidin supplementation on total cholesterol, low-density lipoprotein (LDL), and high-density lipoprotein (HDL) levels in the blood and meat of broiler chickens. Method research was experimental with a completely randomised design (CRD), consisting of 6 treatments and 6 replications. A total of 36 broilers were randomly allocated into six treatment groups using a Completely Randomized Design (CRD): K0 (standard feed), K1 (hypercholesterolemic feed), K2 (Simvastatin 0.1 mg/kg body weight), P1 (Hesperidin 10 mg/kg feed), P2 (Hesperidin 20 mg/kg feed), and P3 (Hesperidin 30 mg/kg feed). The observed parameters included total cholesterol, LDL, and HDL concentrations in serum and meat samples. Data were analysed using one-way Analysis of Variance (ANOVA), and significant differences were further tested using Duncan’s Multiple Range Test at a 5% significance level. The results showed that hesperidin supplementation significantly reduced total cholesterol and LDL levels in both blood and meat compared to the hypercholesterolemic group (p < 0.05). In addition, hesperidin significantly increased HDL levels in serum and meat. These findings suggest that hesperidin has potential as a natural feed additive to improve lipid profiles and enhance the nutritional quality of broiler meat by modulating cholesterol metabolism. Conclusion based on the analysis conducted in this study, the best results were observed in treatment P2 (hesperidin at a dose of 20 mg/kg), which was able to improve meat quality. Furthermore, the contribution of margin analysis showed a positive financial impact for the P2 group.